Response of grain legumes to rhizobial inoculation in two savanna soils of Nigeria - Aliyu, I.; Yusuf, A.A.; Abaidoo, Robert C. (Academic Journals, 2013)
Three inoculation trials with soybean, cowpea and groundnut were conducted on Eutric Cambisols (EC) and Rhodic Nitisols (RN) in a greenhouse. Five rhizobial inoculants: MAR 1495, TSBF Mixture, Legumefix, HiStick and IRJ 2180A were tested on each crop to determine their response to soil type and ability to form symbiotic relationship with the crops. Generally, response to inoculation was found to be significantly higher (P < 0.05) in EC than RN. In soybean and groundnut trials, highest nodulation in both soils was recorded by strain MAR 1495 followed by TSBF Mixture and these were significantly higher (P < 0.05) than other inoculants and control. A similar trend, though only in EC, was observed in N uptake and in nitrogen fixation but no significant difference was observed in dry matter yield. Cowpea trials did not show response to inoculation nor was there difference between the soils. Instead, control treatment surpassed all the inoculated treatments in nodulation at P < 0.05. Nitrogen uptake and N2 fixation of control also surpassed those of inoculated treatments. Rhizobia strains MAR 1495 and TSBF Mixture showed similar ability to improve the productivity of soybean and groundnut thus can be used as common inoculants for the two crops.